THE INFLUENCE OF PROBLEM BASED LEARNING ASSISTED BY PhET COLORADO MEDIA ON STUDENTS’ LEARNING OUTCOMES AND SCIENCE PROCESS SKILLS ON THE MATERIAL OF FORCE AT PUBLIC JUNIOR HIGH SCHOOL 37 MEDAN - Christina Sinaga, Artha; Hardinata, Aristo (ISER (Indonesian Science Education Research), 2024)
This research explores the effects of applying the Problem-Based Learning (PBL) model, supported by PhET Colorado media, on students' learning achievement and science process skills in the topic of force among seventh-grade students at SMP Negeri 37 Medan during the 2024/2025 academic year. The study employs a quasi-experimental approach using a Pretest-Posttest Control Group Design, with two classes selected as the research sample, VII-E (Experimental Class) using PBL with PhET Colorado and VII-F (Control Class) without PBL and PhET Colorado. The sampling technique applied was Purposive Sampling. Data collection was conducted through tests and observations, followed by analysis using the Independent Sample t-test. In the experimental class, the average pretest score was 40, while the posttest score showed a significant improvement, reaching 84, while in the control class, they were 39 and 67. The hypothesis test confirmed a significant effect of PBL with PhET Colorado on students' learning outcomes. Additionally, the final assessment of science process skills revealed that the experimental class achieved a proficiency rate of 79.41%, whereas the control class attained a lower percentage of 39.16%, demonstrating a significant impact of the implemented learning model. Keywords: PBL, PhET, colorado, science, skills